Effect of Volleyball Small Side Games on Body Mass Index and Physiological Conditions on Pre Pubertal Children - Hari, Hari Pamungkas; Kurniawan, Farid Tri; Budijanto, Budijanto; Mardikaningsih, Agusti; Agyanur, Shoffurijal (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2024)
This study aims to determine effect volleyball small side games (SSG) on body mass index (BMI) and physiological conditions in prepubescent children. The method used The Randomized Pretest-Posttest Group Design with a sample of 20 subjects. Research subjects determined based on inclusion and exclusion criteria and divided into experimental and control groups. Experimental group was given SSG volleyball intervention and control group without treatment. BMI measured by the formula BMI and Blood taken 24 hours before the exercise intervention and 24 hours after the intervention. To determine the physiological condition of the subject, the variables used were blood glucose and hemoglobin. SSG volleyball was carried out for 8 weeks with 3x intervention in 1 week. The results of BMI and serum data were analyzed with SPSS 25 with paired sample t-test and independent t-test. The results of this study from an independent t-test between the experimental group and the control group showed a variable value of BMI with a p-value of 0.016 (P<0.05),blood glucose p-value of 0.000 (P<0.05) and a hemoglobin p-value 0.007 (P<0.05). Results this study can be concluded a significant influence of volleyball SSG intervention on changes body mass index and physiological conditions of prepubertal children.